Alamo all-stars ebook A texas tale. - Hale, Nathan (Nathan Hale's Hazardous Tales, 2016)
New York Times Bestselling Series! âThese books are, quite simply, brilliant. . . .Thrilling, bloody, action-packed stories from American history.â â New York Times Â  Learn the thrilling true story of the Texas Revolution and the Battle of the Alamo with the New York Times bestselling graphic novel series! Â  âRemember the Alamo!â That rallying cry has gone down in Texas history. But what, exactly, should we remember? Who were the ragtag group of adventurers behind the famous slogan, and how did they end up barricaded in a fort against a Mexican army? Who survived, who died, and how? Â  In the early 1800s, Native Americans, the Mexican government, and settlers from other areas of the United States were fighting over the territory that would become the Lone Star state. Here vivid illustrationsârendered in black, white, and shades of gray, with tinges of yellowâand witty text tell the story, from Texasâs near wilderness beginnings to the Battle of the Alamo and General Sam Houstonâs ultimate victory over General Antonio LÃ³pez de Santa Anna at the Battle of San Jacinto. Â  Let âNathan Haleâ tell the tale of the Texas fight for independence from the Mexican government. It features the exploits of the notorious Jim Bowie, as well as Stephen Austin, Davy Crockett, and other âall-starâ settlers and soldiers who made the wild frontier of Texas their homeâuntil the bitter end. Â  Nathan Haleâs Hazardous Tales! Read them allâif you dare! One Dead Spy: A Revolutionary War Tale (Nathan Haleâs Hazardous Tales #1) Big Bad Ironclad!: A Civil War Tale (Nathan Haleâs Hazardous Tales #2) Donner Dinner Party: A Pioneer Tale (Nathan Haleâs Hazardous Tales Book #3) Treaties, Trenches, Mud, and Blood: A World War I Tale (Nathan Haleâs Hazardous Tales #4) The Underground Abductor: An Abolitionist Tale about Harriet Tubman (Nathan Haleâs Hazardous Tales #5) Alamo All-Stars: A Texas Tale (Nathan Haleâs Hazardous Tales #6) Raid of No Return: A World War II Tale of the Doolittle Raid (Nathan Haleâs Hazardous Tales #7): Lafayette!: A Revolutionary War Tale (Nathan Haleâs Hazardous Tales #8) Major Impossible: A Grand Canyon Tale (Nathan Haleâs Hazardous Tales #9) Blades of Freedom: A Tale of Haiti, Napoleon, and the Louisiana Purchase (Nathan Haleâs Hazardous Tales #10) Cold War Correspondent: A Korean War Tale (Nathan Haleâs Hazardous Tales #11)